God with us and without us : Volume 1 Oneness in Trinity versus absolute oneness - SHEHADEH, Imad. N (Carlisle Langham Global Library, 2020)
The revelation of the Trinity establishes that the relationship of the one true God with us springs from the relationship within himself, without us. The Trinity is not a problem to be solved, but a beauty to be discovered. Dr Imad N. Shehadeh uses careful exegetical and theological analysis to explore the presentation of the triune God in Scripture and expertly navigate the reader through the errors and pitfalls regarding the Trinity.
Includes bibliographical references and index.
Keywords: Trinity, Simplicity, Antitrinitarianism